Penataan Sistem Pelabuhan Rakyat Di Pelabuhan Tambak Lorok Semarang - Sutini Sutini (Dinamika Bahari, 2020)
This research is primarily aimed at improving the main service system in public ports regarding shipping of goods, ship documents and cargo documents. It maps the service quality dimension to a new set of service characteristics based on the current priorities of the people's shipping companies. Data collected through surveys of public shipping companies and public ports are regressed in the Linear Regression model. The results show that the top two service characteristics that affect customer satisfaction are (1) the quality of the customer service representatives, (2) the quality of digitization and (3) the quality of the sales representatives in that order. This research also shows that the ability to improve the operational system is not in accordance with the standard operating procedures applicable at Tambak Lorok Port, Semarang.